1999
DOI: 10.1182/blood.v93.1.113
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine-Dependent and -Independent Mechanisms of STAT3 Activation by the Human Granulocyte Colony-Stimulating Factor (G-CSF) Receptor Are Differentially Utilized Depending on G-CSF Concentration

Abstract: The granulocyte colony-stimulating factor receptor (G-CSF-R) activates multiple STAT proteins. Although the membrane-proximal cytoplasmic region of the G-CSF-R is necessary and sufficient for activation of STAT1 and STAT5, activation of STAT3 requires the membrane distal region that contains four tyrosines. Although one of these (Y704) has previously been shown to be involved in STAT3 activation from a truncated G-CSF-R derived from a patient with severe chronic neutropenia (SCN), this tyrosine is not required… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(62 citation statements)
references
References 52 publications
3
59
0
Order By: Relevance
“…Subsequently, we assessed the consequences of removal of the internalization domain and substitution of the lysine residues for G-CSF-induced proliferation and differentiation. As demonstrated previously, 32D cells expressing wt G-CSFR proliferated 6-8 days and differentiated into neutrophilic granulocytes from day 6 onwards ( Figure 4D and E) (Ward et al, 1999a). In contrast, 32D cells expressing d749-769 or K5R continued with proliferation in response to G-CSF at the expense of terminal granulocytic differentiation ( Figure 4D and E).…”
Section: Figuresupporting
confidence: 79%
“…Subsequently, we assessed the consequences of removal of the internalization domain and substitution of the lysine residues for G-CSF-induced proliferation and differentiation. As demonstrated previously, 32D cells expressing wt G-CSFR proliferated 6-8 days and differentiated into neutrophilic granulocytes from day 6 onwards ( Figure 4D and E) (Ward et al, 1999a). In contrast, 32D cells expressing d749-769 or K5R continued with proliferation in response to G-CSF at the expense of terminal granulocytic differentiation ( Figure 4D and E).…”
Section: Figuresupporting
confidence: 79%
“…Regardless of the exact composition, this ligand concentration-dependent transition to a higher order complex involving the Ig domain contrasts with other hematopoietin receptors, such as growth hormone receptor, which only requires its CRH region to form a simple, symmetrical 2:1 receptor-ligand complex (13,49). In addition, we have recently shown that the ligand sensitivity for STAT3 activation is ‫1ف‬ log higher than for activation of STATs 1 and 5 from the wild-type G-CSF-R (22). This suggests that different intracellular signaling complexes are also formed depending on ligand concentration: at low concentrations, one that can activate STAT3, and at high concentrations, one that can activate all three STATs.…”
Section: Discussionmentioning
confidence: 84%
“…When expressed in myeloid cells, these truncated receptors transduce a strong growth signal but are defective in maturation signaling (26,28). This is due to sustained receptor activation caused by defective internalization and an altered balance of STAT activation (22,29,30). However, in SCN patients with this mutation, G-CSF treatment is able to reverse the neutropenia (25)(26)(27).…”
mentioning
confidence: 99%
“…On the other hand, investigations in Ba/F3 cells and primary bone marrow cultures have established that at saturating G-CSF concentrations STAT3 can also be activated via a tyrosine-independent route. The latter mechanism requires the presence of the membrane-distal region of the G-CSF-R (77,78). Although the exact nature of this tyrosine independent route is still unclear, it was suggested that different mechanisms for STAT3 activation might be involved in the control of steady-state granulopoiesis at a low G-CSF level (mainly tyrosinedependent) versus "emergency" granulopoiesis initiated by an increased level of G-CSF (tyrosine-independent) (77).…”
Section: Jak/stat Pathwaysmentioning
confidence: 99%